2015
DOI: 10.1097/sla.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Total Mesorectal Excision With Coloanal Anastomosis for Rectal Cancer

Abstract: Transanal extraction of the rectal specimen did not compromise oncologic and functional outcome after laparoscopic surgery for low rectal cancer and seems as a safe option to preserve the abdominal wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
2
19
0
2
Order By: Relevance
“…Kim et al [27] and Denost et al [25] reported the DFS of patients between the two groups. Pooled results suggested no evidence of a significant difference in DFS between the two groups (HR=0.88, 95 % CI [0.49, 1.57], p=0.67), and there was no remarkable heterogeneity among studies (p= 0.98, I 2 =0 %) (Fig.…”
Section: Dfsmentioning
confidence: 97%
See 2 more Smart Citations
“…Kim et al [27] and Denost et al [25] reported the DFS of patients between the two groups. Pooled results suggested no evidence of a significant difference in DFS between the two groups (HR=0.88, 95 % CI [0.49, 1.57], p=0.67), and there was no remarkable heterogeneity among studies (p= 0.98, I 2 =0 %) (Fig.…”
Section: Dfsmentioning
confidence: 97%
“…Apart from the study of Denost et al [25], other studies all included the duration of hospital stay. We considered that laparoscopic resection with NOSE could significantly reduce the duration of hospital stay (WMD=−0.62 days, 95 % CI [−0.95, −0.28], p<0.01).…”
Section: Duration Of Hospital Staymentioning
confidence: 99%
See 1 more Smart Citation
“…5), wurde in diesem Zusammenhang ebenfalls kontrovers diskutiert. Einer aktuellen französischen Studie nach besteht hierdurch jedoch kein erhöhtes Lokalrezidivrisiko [28].…”
Section: Diskussionunclassified
“…Трансанальный способ удаления препарата служит промежуточным шагом к транслю-минальным операциям в колоректальной хирургии, и, по мнению некоторых авторов, не уступает минила-паротомии [39]. Исследователи, придерживающиеся противоположной точки зрения, указывают на более высокую частоту осложнений, связанных с транса-нальным извлечением препарата [40].…”
unclassified